Diseño de la documentación para el sistema de gestión de calidad bajo los requisitos de la Norma NTC ISO 9001:2015 para la empresa British American Tabacco de la ciudad de Bogotá. (2023)
In this project, the results of the design of the documentation for the Quality Management System of the British American Tabacco company are delivered, in accordance with the requirements of NTC-ISO 9001:2015, for which four stages were developed: which are consistent with the specific objectives. To start in stage I, referring to the diagnosis of the current situation of the management system, for this purpose, the mission, vision and organizational chart of the company were developed, as well as a checklist based on the requirements of the ISO 9001 standard: 2015, obtaining as results a compliance of 41%. Based on the results obtained, the subsequent stages were prepared, in stage II the risks and opportunities were established using a SWOT matrix, to then be evaluated following the proposed procedure and risk matrix based on the weaknesses and threats detected. In the third stage, the required documentation was established, in which the quality policy, strategic objectives, process map for the identification of interrelationships and subsequent characterization where the inputs, activities and outputs of each process are evidenced. , matrix of responsibilities for the SGC, development of training procedures, service, corrective and preventive actions, record formats, as well as a dashboard of indicators for the measurement and monitoring of the factors that influence the management of the system. Finally, the cost-benefit relationship is established based on the internal documentation required based on NTC-ISO 9001:2015, with 82% compliance and significant savings of 68% for the company